HEALTH EDUCATION ON MATERNAL KNOWLEDGE AND ATTITUDES IN BABY MASSAGE INDEPENDENTLY - Candra Dewinataningtyas nataningtyas; Nareswari Diska Nugraha Nugraha (Indonesian Midwifery and Health Sciences Journal)
Background: Baby massage is a comfortable form of communication between mother and baby. Benefits of regular baby massage with proper techniques include increased baby weight gain, improved breast milk production, reduced maternal anxiety, and stronger bonding. Method: Quantitative research using a cross-sectional approach. Data analysis was conducted using univariate and bivariate techniques with chi-square statistical tests. The sample in this study consisted of 45 mothers with babies aged 0–12 months in Kedak Village, Semen, Kediri Regency. Sampling technique with accidental sampling. Respondents were given a questionnaire before and after participating in a health education session conducted using audiovisual media and leaflets. Result:The bivariate analysis using the chi-square test showed the value of Asymp. A significant relationship was found between pre-health education and the knowledge and attitude of mothers in massaging their baby independently, with a p-value of 0.000. Post-health education, the Asymp. significance level of p-value 0.001 indicates a relationship between mothers' knowledge and their attitude towards independently massaging their babies after health education. Conclusion: There is a relationship between health education and mothers' knowledge and attitude towards independently massaging their babies.